EVALUATING OF DROUGHT STRESS TOLERANCE BASED ON SELECTION INDICES IN TURKISH BREAD WHEAT LANDRACES - M. Akçura; F. Partigoç; Y. Kaya (Journal of Animal and Plant Sciences, 2011)
The objective of this study was to evaluate the ability of several selection indices to identify drought tolerant/resistant genotypes under different conditions of Konya. Thirty six bread wheat genotypes (twenty four pure lines from Turkish bread wheat landraces and twelve modern bread wheat cultivars) were evaluated under both moisture stress (rainfed) and non stress (irrigated) conditions using a “randomized complete block design” with three replications. Nine drought tolerance indices including yield stability index (YSI), yield index (YI), superiority index (Pi), stress tolerance index (STI), geometric mean productivity (GMP), stress susceptibility index (SSI), mean productivity (MP), stress tolerance (TOL), harmonic mean (HM) and linear regression coefficient (bi) were calculated.  The indices were adjusted based on grain yield under drought condition (Ys) and normal conditions (Yp). SSI is suggested as useful indicator for wheat breeding where the stress is severe while MP, GMP, TOL HM and STI are suggested if the stress is less severe. Biplot analysis was used to explain relationship between grain yield and drought indices. Karahan-99, Bayraktar-2000, Gerek-79, PL-7, Sönmez-2000, Kıraç-66 and PL-5 were the superior genotypes for both rainfed and irrigated conditions with high PC1 and low PC2. PL-25, PL-13 and PL-23 with high PC2 were more suitable for rainfed than irrigated conditions.
Keywords: biplot analysis; drought indices; Turkey; winter bread wheat landraces.